Metabolic Analysis of Root, Stem, and Leaf of Scutellaria baicalensis Plantlets Treated with Different LED Lights - Hyeon-Ji Yeo; Chang-Ha Park; Soo-Yun Park; Sun-Ok Chung; Jae-Kwang Kim; Sang-Un Park (Plants, 2021)
Light emitting diodes (LEDs) have recently been considered an efficient artificial light source in plant factories for enhancing plant growth and nutritional quality. Accordingly, this study aimed to review blue, red, and white LED light sources for efficiency and length of the growing period to produce seedlings of Scutellaria baicalensis with high nutritional value. The roots, stems, and leaves of S. baicalensis seedlings were grown under different LED lights and harvested after two and four weeks, and analyzed using high-performance liquid chromatography and gas chromatography time-of-flight mass spectrometry to identify and quantify primary and secondary metabolites. Roots, particularly in the seedlings treated with white LEDs were determined to contain the greatest concentrations of the representative compounds present in S. baicalensis: baicalin, baicalein, and wogonin, which show highly strong biological properties compared to the other plant organs. A total of 50 metabolites (amino acids, sugars, sugar alcohols, organic acids, phenolic acids, and amines) were detected in the roots, stems, and leaves of S. baicalensis seedlings, and the concentrations of primary and secondary metabolites were generally decreased with the increasing duration of LED illumination. Therefore, this study suggests that white LED light and a 2-week growing period are the most efficient conditions for the production of baicalin, baicalein, and wogonin.